199. Evaluation of beam's attenuation using the Delta4 Discover transmission detector in various treatment application. (December 2018) - Oliviero, C.; D'Avino, V.; Conson, M.; Pacelli, R.; Romano, C.; Franza, N.; Clemente, S.
Abstract : Purpose: Delta4 Discover (ScandiDos, Uppsala, Sweden) is a new device developed in order to monitor online complex radiation techniques such as volumetric-modulated arc therapy (VMAT). It can be inserted between the radiation source and the patient so it can potentially impact the beam quality that the patient receives. The aim of this work is to investigate, in terms of beam's attenuation, the feasibility of using Discover transmission array[1] . Methods: 9 VMAT treatment plans, generated using Pinnacle3's SmartArc algorithm v.9.10 (Philips Fitchburg, USA), for various treatment sites, were delivered using Delta4 Phantom+ (ScandiDos, Uppsala, Sweden). The response, with and without the Discover mounted on the linac was evaluated. All plans were delivered on a Varian TrueBeam STx equipped with HD MLC. For phantom verification, plans were recalculated replacing the patient planning CT scan with a phantom CT scan. Dose distributions of each plan delivered with and without Discover were verified using the Delta4 Phantom + and compared to calculated dose. Results: Analyzing dose difference profiles, the Relative Dose Difference, between the measured dose relative to both configurations, showed that the absorption of beam radiation observed was on average about 1%. About Median Dose Deviation between the calculated and measured dose for both configurations we found that the all Median Dose Deviation shift values are ranging from 0.2% to 1.3%. Conclusions: The thin transmission detector Delta4 Discover shows good potential for real time quality assurance. The minimal attenuation observed potentially allows for a real time verification and independent monitoring of complex VMAT deliveries during patient treatment.